Response of adenocarcinoma of the uterine cervix to chemoradiotherapy - KAIDAR-PERSON, ORIT (Oncol Lett, 2015)
The aim of the current retrospective study was to investigate the response of advanced cervical adenocarcinoma (AC) to definitive chemoradiotherapy. Uterine cervical cancer is one of the most common cancer types among females, with squamous cell carcinoma (SQCC) being the most prevalent histological type. The incidence of cervical AC and its variants has markedly increased in recent decades. The current understanding with regard to the treatment of cervical cancer has been established through studies in which the majority of the patients suffered from SQCC, while only a limited number of studies have focused on the treatment of AC. Therefore, the optimal treatment for uterine cervical AC remains unclear. In the present study, data were collected from the medical files of patients who were diagnosed with advanced uterine cervical AC and treated with chemoradiotherapy between 1998 and 2013. Data were also collected from a group of patients with SQCC for comparison with AC patients in terms of response and survival. A total of 68 uterine cervical cancer cases were included, including 29 AC patients and 39 SQCC patients. Compared with the SQCC subgroup, a higher number of AC patients required surgery following chemoradiotherapy due to a lack of response to the initial treatment (5% vs. 31%, respectively; P=0.0065). After a median follow-up period of 10 years, patients with AC exhibited shorter overall survival (7.4 years vs. 11 years for AC and SQCC groups, respectively; P=0.01). Differences in recurrence (40.7% vs. 34.4%; P=0.79) and disease-free interval (1.2 years vs. 2 years; P=0.11) were not statistically significant. The results indicated that cervical AC is less responsive to chemoradiotherapy compared with SQCC.